Observer repeatability and interscan reproducibility of 18F-sodium fluoride coronary microcalcification activity - Tzolos, Evangelos (J Nucl Cardiol, 2022)
BACKGROUND: We aimed to establish the observer repeatability and interscan reproducibility of coronary (18)F-sodium-fluoride positron emission tomography (PET) uptake using, a novel semi-automated approach, coronary microcalcification activity (CMA). METHODS: Patients with multivessel coronary artery disease underwent repeated hybrid PET and computed tomography angiography (CTA) imaging (PET/CTA). CMA was defined as the integrated standardized uptake values (SUV) in the entire coronary tree exceeding 2 standard deviations above the background SUV. Coefficients of repeatability between the same observer (intraobserver repeatability), between 2 observers (interobserver repeatability) and coefficient of reproducibility between 2 scans (interscan reproducibility), were determined at vessel and patient level. RESULTS: In 19 patients, CMA was assessed twice in 43 coronary vessels on two PET/CT scans performed 12±5 days apart. There was excellent intraclass correlation for intraobserver and interobserver repeatability as well as interscan reproducibility (all ≥0.991). There was 100% intraobserver, interobserver and interscan agreement for the presence (CMA>0) or absence (CMA=0) of coronary(18)F-NaF uptake. Mean CMA was 3.12±0.62 with coefficients of repeatability of ≤10% for all measures: intraobserver 0.24 and 0.22, interobserver 0.30 and 0.29 and interscan 0.33 and 0.32 at a per-vessel and per-patient level respectively. CONCLUSIONS: CMA is a repeatable and reproducible global measure of coronary atherosclerotic activity.